Proteomic, metabolomic and lipidomic profiles in community acquired pneumonia for differentiating viral and bacterial infections - Samuel Rischke; Robert Gurke; Ann-Sophie Zielbauer; Nicole Ziegler; Lisa Hahnefeld; Michaela Köhm; Aimo Kannt; Maria JGT Vehreschild; Gerd Geisslinger; Gernot Rohde; Carla Bellinghausen; Frank Behrens; et al. (Scientific Reports)
Abstract Community-acquired pneumonia (CAP) has a significant impact on public health, especially in light of the recent SARS-CoV-2 pandemic. To enhance disease characterization and improve understanding of the underlying mechanisms, a comprehensive analysis of the plasma lipidome, metabolome and proteome was conducted in patients with viral and bacterial CAP infections, including those induced by SARS-CoV-2. Lipidomic, metabolomic and proteomic profiling were conducted on plasma samples of 69 patients suffering either from viral or bacterial CAP. Lipid and metabolite analyses were LC-MS-based, while proteomic analyses were performed using multiple panels of the Olink platform. Statistical methods, machine learning and pathway analyses were conducted investigating differences between the infection types. Through comparison of the bacterial and viral pathogen groups, distinct signatures were observed in the plasma profiles. Notably, linoleic acid-derived inflammation signaling metabolites (EpOME and DiHOME) were increased in viral CAP compared to bacterial CAP. Similarly, proteins involved in cellular immune response and apoptosis (LAG-3 and TRAIL) showed elevated levels in viral CAP, while bacterial CAP exhibited notable elevation in pattern-recognizing receptors (CLEC4D and EN-RAGE). Additionally, within the lipidomic profile at baseline, several lipids displayed notable differences between viral and bacterial pneumonia, including bile acids (GCA, TCA, TCDCA), various tri- and diglycerides (TGs and DGs), and several phosphatidylcholines (PCs). These findings hold promise for facilitating the differential diagnosis of viral and bacterial pulmonary infections based on the systemic lipidome, metabolome and proteome, enabling timely treatment decisions. Additionally, they highlight potential targets for drug research, advancing therapeutic interventions in CAP. By providing valuable insights into the molecular characterization of CAP, this study contributes to the improvement of understanding the disease and, ultimately, the development of effective treatment strategies.